(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
With the rise to power of the German National Socialists, cultural and artistic activities were threatened. The Bauhaus school was raided on two of its campuses: Dessau and Berlin; During this historical period the art scene community, be it painters, sculptors, architects, photographers, etc., dispersed throughout Europe, then to other parts of the globe. After the Second World War; Otto Steinert takes on the task of launching the ideal of reborn German photography from the ashes of the war conflict and positioning his country as the spearhead of creative activity through the use of a camera as a recreational and creative tool. To do this, look at the photographic activity that took place at the Bauhaus, at the postulates of MoholyNagy, at the work that Peterhans had as a photography teacher. As well as the influences that Teutonic photography had from the avantgarde of the early 20th century. With this, he presents a program of photographic creation that Steinert calls absolute, which acquires the character of formula and method, on which all the great photographers who were involved in this movement of subjective photography, which until today, would be based. Today it has an impact not only on European photography, but its concepts have an impact in Latin America in the way of conceiving photography as a utilitarian, artistic and design tool.